Autoridade musical pedagógica: Orlando Vieira Leite - Gomes, Sabrina Linhares (2018)
The present work proposes the analysis of the musical trajectory of Orlando Vieira Leite in order to understand his pedagogical actions, investigating how the symbolic power and the social actions of maestro Orlando Vieira Leite collaborated with the construction of the field of musical education in the city of Fortaleza and in Brasília, considering the subject as an authority. We sought to explain how the process of construction of the musical habitus of maestro Orlando Vieira Leite occurred, how his educational process as a music educator took place, how he became an authority in the city of Fortaleza and Brasília and how the mentioned was able to contribute effectively with the field of Musical Education of the city of Fortaleza and in Brasilia through its symbolic power and its social actions. We investigated the process of formation of the musical habitus of Orlando Vieira Leite, we identified the musical educator 's constitution with reference to the musical educator in question, we studied the actions of reference that contributed to the formation of the musical education field of the city of Fortaleza (1956 - 1971) and in Brasília (1971 - 1991) as a reference musical educator, we understood his eradication of the city of Fortaleza and the impact of his pedagogical actions in Brasilia, city in which the maestro settled and evaluated the contributions of Orlando Vieira Leite in the formation of the musical education field in the city of Fortaleza and its due impacts in the following years. Through this study we verified the transformation of Orlando Vieira Leite into a musical educator, later into a musical educator reference and we conclude that it became a Pedagogical Musical Authority.